LAW ENFORCEMENT AGAINST FOREIGNERS USING FAKE PASSPORTS - Akbar, Muhammad Aulia; Marbun, Warasman; Saefullah (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
The phenomenon of many foreigners still entering Indonesia has caused various problems, including the use of fake passports. In the field of supervision immigration Lots happen case forgery letter travel by foreigners. Although Constitution immigration arrange punishment serious crime, in reality Lots case forgery document journey Already brought to court, but the verdict Still too light on demands of the Public Prosecutor, as well as still there are foreigners who have already managed to get in to the Indonesian region with use letter the alleged journey fake. Of course just, thing This No cause effect deterrent for foreigners who try? to fake document travel in Indonesia. The Problem Is How enforcement law against foreigners who use it passport false For enter and/ or go out from the territory of Indonesia in the Decision Number 126/ Pid.Sus /2021/PT.BTN and Decision Number 1234/ Pid.Sus /2020/PN JKT.SEL? How? effort prevention and eradication use passport fake by foreigners? The research method is normative legal research. The conclusion is Legal regulation of Foreign Citizens who commit the crime of passport forgery is regulated in Articles 263 to 264 of the Criminal Code in Indonesia regulated in Law No. 6 of 2011 regulated in CHAPTER XI Articles 126-130 and in Government Regulation No. 31 of 2013 concerning the Implementing Regulations of Law No. 6 of 2011 concerning Immigration and the efforts made by the Directorate General of Immigration to prevent passport forgery by Foreign Citizens, namely by forming TIMPORA (Foreigner Supervision Team) by forming a foreigner supervision team, immigration can synergize with related agencies to prevent foreigners who will make fake Indonesian passports.